Effects of Social Capital on Cocoa Production in Cameroon - Mbu Daniel Tambi; Muluh Mildred Lum (International Journal of Business Economics (IJBE), 2020)
The importance of social capital is another new stylized fact in promoting agriculture The objectives targeted are: to examine the impact of social capital in the enhancement of cocoa production, explore the determinants of social capital and to determine the challenges faced by producers in Santchou cocoa zone. Methodologically, we have constructed a social capital indicator using Multiple Correspondence Analyses. Primary data is collected in the zone and probit model use to estimate the result. The result revealed a strong correlation between social capital and agricultural production while the level of education, gender, marital status, financial status, experience in farm activity, household size and agricultural training are strongly corroborating with social capital. In addition, farm size, level of education, application of farm inputs (pesticides and fertilizers), modern equipment, climate change, access to credit and land tenure system are observed to be the major challenges of farmers in this cocoa zone. We suggest that the decision makers should promote social networking among farmers in the zone.